Pengaruh Cash On Delivery dan Paylater terhadap Kepuasan Pelanggan E-Commerce Shopee - Mustaqim, Mirza; Irawan, Hengki; Ekawati, Farida (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2023)
The phenomenon of the development of technology and science has influenced the daily behavior of people in Indonesia by becoming easier and faster. No exception for e-commerce which has emerged and developed rapidly influencing people's behavior. The Shopee application takes advantage of the opportunities for technological developments to attract the attention of Indonesian customers, especially with unique features on its platform. With Shopee, shopping becomes easier. And this convenience is really provided by Shopee, including the choice of COD and Paylater features with the aim of providing customer satisfaction. The study aims to determine the effect of COD and Paylater on Customer Satisfaction. Descriptive quantitative research design. The number of samples is 91 and the analysis technique is multiple linear regression. The conclusion is that the COD and Pay Later signs are 0.000 <0.05, so both have an effect on customer satisfaction.